Why Do Firms Pay Dividends?: Evidence from an Early and Unregulated Capital Market - Turner, John D.; Ye, Qing; Zhan, Wenwen (Review of Finance, 2013)
Abstract Why do firms pay dividends? To answer this question, we use a hand-collected data set of companies traded on the London stock market between 1825 and 1870. As tax rates were effectively zero, the capital market was unregulated, and there were no institutional stockholders, we can rule out these potential determinants ex ante. We find that, even though they were legal, share repurchases were not used by firms to return cash to shareholders. Instead, our evidence provides support for the information–communication explanation for dividends, while providing little support for agency, illiquidity, catering, or behavioral explanations.